Clinical outcomes of prostate cancer patients in Yokosuka City, Japan: A comparative study between cases detected by prostate‐specific antigen‐based screening in Yokosuka and those detected by other means. (23rd May 2015) - Sakai, Naoki; Taguri, Masataka; Kobayashi, Kazuki; Noguchi, Sumio; Ikeda, Shigeru; Koh, Hideshige; Satomi, Yoshiaki; Furuhata, Akihiko
Abstract Objectives To investigate whether prostate‐specific antigen‐based screening reduced the prostate cancer mortality rate in Yokosuka, Japan. Methods We carried out a cohort study, in which we compared clinical outcomes between patients detected by prostate‐specific antigen‐based screening (S group n = 524) versus those detected by other means (NS group n = 1044). Clinical and pathological factors were evaluated using Cox regression analyses and the Kaplan–Meier method. Results A total of 1.5% (8/524) of patients in the S group and 6.7% (70/1044) of those in the NS group died from prostate cancer during follow up. A total of 8.0% (42/524) of patients in the S group and 11.4% (119/1044) in the NS group died from other causes. The 10‐year cancer specific survival rates of the S and NS groups were 97% and 86%, respectively (P < 0.001). The median age was significantly lower in the S group than the NS group: 71 and 73 years, respectively (P < 0.001). The rate of Gleason score 8–10 was significantly lower in the S group than the NS group: 9.7% and 16.7%, respectively (P < 0.001). The rate of patients with metastasis or prostate‐specific antigen 100 ng/mL or more was significantly lower in the S group than the NS group: 7.8% and 23.0%, respectively (P < 0.001). On multivariate analysis, Gleason score 8–10 compared with Gleason score 6 was independently associated with cancer‐specific survival (hazard ratio 4.808, 95% confidence interval 1.044–22.14, P = 0.044). Conclusions Prostate‐specific antigen‐based population screening in Yokosuka City might help to reduce the prostate cancer mortality rate.